Acetylcholinesterase reactivators (HI-6, obidoxime, trimedoxime, K027, K075, K127, K203, K282): structural evaluation of human serum albumin binding and absorption kinetics - Zemek, Filip; Zdarova, Jana Karasova; Sepsova, Vendula; Kuca, Kamil (International journal of molecular sciences, 2013)
Acetylcholinesterase (AChE) reactivators (oximes) are compounds predominantly targeting the active site of the enzyme. Toxic effects of organophosphates nerve agents (OPNAs) are primarily related to their covalent binding to AChE and butyrylcholinesterase (BChE), critical detoxification enzymes in the blood and in the central nervous system (CNS). After exposure to OPNAs, accumulation of acetylcholine (ACh) overstimulates receptors and blocks neuromuscular junction transmission resulting in CNS toxicity. Current efforts at treatments for OPNA exposure are focused on non-quaternary reactivators, monoisonitrosoacetone oximes (MINA), and diacylmonoxime reactivators (DAM). However, so far only quaternary oximes have been approved for use in cases of OPNA intoxication. Five acetylcholinesterase reactivator candidates (K027, K075, K127, K203, K282) are presented here, together with pharmacokinetic data (plasma concentration, human serum albumin binding potency). Pharmacokinetic curves based on intramuscular application of the tested compounds are given, with binding information and an evaluation of structural relationships. Human Serum Albumin (HSA) binding studies have not yet been performed on any acetylcholinesterase reactivators, and correlations between structure, concentration curves and binding are vital for further development. HSA bindings of the tested compounds were 1% (HI-6), 7% (obidoxime), 6% (trimedoxime), and 5%, 10%, 4%, 15%, and 12% for K027, K075, K127, K203, and K282, respectively.
Keywords: Protein Binding; Male; Adsorption; Rats, Wistar; sérový albumin; mužské pohlaví; potkani Wistar; Acetylcholine; Serum Albumin; adsorpce; acetylcholinesterasa; Cholinesterase Reactivators; krysa rodu Rattus; vazba proteinů; organofosfáty; Animals; Catalytic Domain; zvířata; Rats; reaktivátory cholinesterasy; centrální nervový systém; acetylcholin; nervosvalové spojení; Central Nervous System; Acetylcholinesterase; katalytická doména; Neuromuscular Junction; Organophosphates